The genus Macrostemum Kolenati 1859 (Trichoptera: Hydropsychidae) in the Neotropical Region: Description of two new species, taxonomic notes, distributional records and key to males - França, Diogo; Paprocki, Henrique; Calor, Adolfo R. (Zootaxa, 2013)
The genus Macrostemum Kolenati contains 105 described species, with 15 valid species in the Neotropical region. The adults are recognized principally by wing membranes strongly marked with dark and light colors. The Neotropical species of Macrostemum were described based on the wing colors patterns and body morphology. In this paper we present a taxonomic study of the Neotropical species, descriptions of two new species from Brazil, distributional records and a key to males. The male of Macrostemum negrense Flint 1978 is described for the first time. Names of three Neotropical species, M. ramosum (Navás 1916), M. trigramma (Navás 1916), and M. triste (Navás 1916) are designated nomina dubia.